20th Anniversary of Geo-Heat Center - Lienau, P. J. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1995)
The beginning of the Geo-Heat Center (GHC) can be traced to an international conference held on geothermal energy at the Oregon Institute of Technology (OIT) campus during October of 1974. The meeting was organized to review nonelectric, multipurpose uses of geothermal energy in Hungary, Iceland, New Zealand, the United States and Russia (U.S.S.R). As a result of the conference and interest in the need to exchange and disseminate information on low-to moderate-temperature resources and their utilization, the Geo-Heat Center (first known as the Geo-Heat Utilization Center) was established in 1975. Initial funding was provided by the Pacific Northwest Regional Commission (PNRC), a branch of the Executive Department of the Governors of the states of Oregon, Washington and Idaho. A sum of $3,000 was granted to distribute information to participants of the October 1974 international conference